Ecotoxicology, Ecological Risk Assessment and Multiple Stressors - Arapis, Gerassimos; Goncharova, Nadezhda; Baveye, Philippe; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
The science of ecotoxicology and the practice of ecological risk assessment are evolving rapidly. Ecotoxicology as a subject area came into prominence in the 1960s after the publication of Rachel Carson's book on the impact of pesticides on the environment. The rise of public and scientific concern for the effects of chemical pollutants on the environment in the 1960s and 1970s led to the development of the discipline of ecotoxicology, a science that takes into account the effects of chemicals in the context of ecology. Until the early 1980s, in spite of public concern and interest among scientists, the assessment of ecological risks associated with natural or synthetic pollutants was not considered a priority issue by most government. However, as the years passed, a better understanding of the importance of ecotoxicology emerged and with it, in some countries, the progressive formalization of an ecological risk assessment process. Ecological risk assessment is a conceptual tool for organizing and analyzing data and information to evaluate the likelihood that one or more stressors are causing or will cause adverse ecological effects. Ecological risk assessment allows risk managers to consider available scientific information when selecting a course of action, in addition to other factors that may affect their decision (e. g. , social, legal, political, or economic). Ecological risk assessment includes three phases (problem formulation, analysis, and risk characterization).
THE SCIENCE OF ECOTOXICOLOGY: ESTABLISHING THE INTERNATIONAL BASIS FOR ECOLOGICAL RISK ASSESSMENT -- CURRENT DEVELOPMENTS IN ECOTOXICOLOGY AND ECOLOGICAL RISK ASSESSMENT -- FROM MOLECULE TO ECOSYSTEMS: ECOTOXICOLOGICAL APPROACHES AND PERSPECTIVES -- PROTECTING THE ENVIRONMENT AGAINST IONISING RADIATION: THE PATH PROPOSED BY (3z(BICRP(3y(B, ITS ORIGINS AND ANALYSIS -- ECOEPIDEMIOLOGY: A MEANS TO SAFEGUARD ECOSYSTEM SERVICES THAT SUSTAIN HUMAN WELFARE -- PERCHLORATE: ECOLOGICAL AND HUMAN HEALTH EFFECTS -- GENETIC ECOTOXICOLOGY AND RISK ASSESSMENT: AN OVERVIEW -- ECOLOGICAL RISK ASSESSMENT AND MULTIPLE STRESSORS -- SCIENTIFIC BASIS FOR ECOTOXICOLOGY, ECOLOGICAL RISK ASSESSMENT AND MULTIPLE STRESSORS: CANADIAN EXPERIENCE IN DEFINING ACCEPTABLE RISK LEVELS FOR INFRASTRUCTURE -- RISK ASSESSMENT IN ROMANIA: FROM LEGISLATION TO NEEDS AND POSSIBILITIES -- ECOTOXICOLOGICAL RISK ASSESSMENT FOR PLANT PROTECTION PRODUCTS IN EUROPE -- ASSESSMENT OF ECOLOGICAL RISK CAUSED BY THE LONG-LIVING RADIONUCLIDES IN THE ENVIRONMENT -- EFFECTS OF CONTAMINANT EXPOSURE ON PLANTS: RADIOLOGICAL PROTECTION OF THE ENVIRONMENT IMPLICATIONS FOR ECOTOXICOLOGY AND -- RISK ASSESSMENT: RADIOACTIVE CONTAMINATED FOOD PRODUCTS AND EXPOSURE DOSE OF THE POPULATION -- METHODS AND TOOLS IN ECOTOXICOLOGY AND ECOLOGICAL RISK ASSESSMENT -- A HABITAT SUITABILITY EVALUATION TECHNIQUE AND ITS APPLICATION TO ENVIRONMENTAL RISK ASSESSMENT -- THE QND MODEL/GAME SYSTEM: INTEGRATING QUESTIONS AND DECISIONS FOR MULTIPLE STRESSORS -- THE MEDAKA FISH: AN EXPERIMENTAL MODEL IN ENVIRONMENTAL TOXICOLOGY ITS USE FOR THE SURVEY OF MICROALGAL TOXINS: PHYCOTOXINS AND CYANOTOXINS -- CYTOGENETIC EFFECT OF RADIOACTIVE OR CHEMICAL CONTAMINATION ON SPRING BARLEY INTERCALARY MERISTEM CELLS -- WATER POLLUTION INDICATORS OF SUSTAINABILITY IN EUROPE, AND THEIR APPLICATION TO COASTAL WATER QUALITY EVALUATION IN ITALY -- APPLICATION OF GIS TECHNOLOGIES IN ECOTOXICOLOGY: A RADIOECOLOGICAL CASE STUDY -- AMBIENT OZONE PHYTODETECTION WITH SENSITIVE CLOVER (TRIFOLIUM SUBTERRANEUM L. CV. GERALDTON) IN UKRAINE -- ECOTOXICOLOGY AND TOXICITY MONITORING -- ALTERATIONS OF AGROECOSYSTEMS IN GREECE THROUGH PESTICIDE USE. THE (3z(BPHALARIS CASE(3y (B-- CONTRIBUTION TO ECOLOGICAL SAFETY THROUGH SEGMENTED INTEGRATED PEST MANAGEMENT IN GREECE -- A PRELIMINARY STUDY OF TOXICITY BY BIOASSAY OF THE WASTES OF PULP AND PAPER PRODUCTION UNITS -- AIR POLLUTION ASSESSMENT IN VOLOS COASTAL TOWN, GREECE -- TROPOSPHERIC OZONE MEASUREMENTS IN THE TATRA MOUNTAINS AND ITS EFFECTS ON PLANTS -- LONG-TERM MONITORING OF TROPOSPHERIC OZONE IN KYIV, UKRAINE: FORMATION, TEMPORAL PATTERNS AND POTENTIAL ADVERSE EFFECTS -- WORKING GROUP SUMMARIES -- A FRAMEWORK FOR MULTI-CRITERIA DECISIONMAKING WITH SPECIAL REFERENCE TO CRITICAL INFRASTRUCTURE: POLICY AND RISK MANAGEMENT WORKING GROUP SUMMARY AND RECOMMENDATIONS -- HINTS ON ECOTOXICOLOGY AND ETHICS -- METHODS AND TOOLS IN ECOTOXICOLOGY AND ECOLOGICAL RISK ASSESSMENT WORKING GROUP SUMMARY.s
Keywords: Life sciences; Environmental sciences; Biochemistry; Radiation protection; Radiation -- Safety measures; Environmental health; Air pollution; Life Sciences; Biochemistry, general; Environmental Science and Engineering; Atmospheric Protection/Air Quality Control/Air Pollution; Effects of Radiation/Radiation Protection; Environmental Monitoring/Analysis.; Environmental Health; Electronic books